Design and Development of Microcontroller Based Rainfall Monitoring Tools with Real-Time Data via Telegram - Sujono, Sujono; Sufaidah, Siti; Nur hidayah, Lailatul (Computech : Jurnal Ilmiah Teknologi Informasi dan Komunikasi, 2024)
Rainfall monitoring is an important aspect of meteorology and water resources management. The development of a microcontroller-based rainfall monitoring device that can transmit data in real-time through the Telegram application offers an effective and efficient solution to overcome the constraints of manual monitoring. This research aims to design and build a rainfall monitoring system that uses a microcontroller as the main controller and the Twilio platform as a data transmission service via Telegram. This tool is designed to measure rainfall intensity using a hall effect sensor, which is then processed by a microcontroller. The rainfall data obtained will be sent to the user's device via Telegram message. This system is expected to provide accurate and timely information to users, so that it can be used in various applications such as agriculture, flood monitoring, and water resource management. The test results show that this rainfall monitoring tool is able to send data quickly, this tool is expected to increase efficiency and effectiveness in rainfall monitoring and make a significant contribution in the field of meteorology and environmental management.